Fluorescent sensing of non-steroidal anti-inflammatory drugs naproxen and ketoprofen by dansylated squaramide-based receptors. Issue 14 (20th March 2023) - Picci, Giacomo; Aragoni, M. Carla; Arca, Massimiliano; Caltagirone, Claudia; Formica, Mauro; Fusi, Vieri; Giorgi, Luca; Ingargiola, Filippo; Lippolis, Vito; Macedi, Eleonora; Mancini, Luca; Mummolo, Liviana; et al.
Abstract : Bis-squaramide receptors L1–L4 bearing a dansyl moiety were considered as fluorescent probes for non steroidal antinflamatory drugs naproxene and ketoprofen. Abstract : Bis-squaramide receptors L1–L4 bearing a dansyl moiety were synthesised and their potential applications as fluorescent probes towards non steroidal anti-inflammatory drugs naproxen and ketoprofen was investigated. A detailed photophysical characterization in CH3 CN/DMSO solution (9 : 1 v/v) was conducted and demonstrated that the two macrocyclic receptors L1 and L2 show good sensitivity towards ketoprofen with an ON–OFF fluorescent response, while the two open chain receptors L3 and L4 behave similarly with the three guests considered. DFT theoretical calculations carried out on L2 and L4 as model receptors allowed to propose a possible coordination mode towards the guests. Finally, 1 H-NMR spectroscopy in DMSO- d 6 /0.5% water solution demonstrated that the four receptors interact with the considered guests via H-bonds.